Mandat Ilahi tentang Memberitakan Kerajaan Allah - Lucky Antonio (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
AbstractThe divine mandate given to man by God from the very beginning of creation was to rule the world(Gen. 1:27). The foundation of God’s Kingdom has already existed since its creation. After man fellinto sin, there was enmity between the serpent, the women, and their respective offspring (Gen. 3:6-7). God’s promise that the serpent will be crushed pointed to the coming of the Messiah and theassurance of victory (Gen. 3:15). The divine mandate to proclaim the kingdom of God can not behindered by anyone and needs to be known by every believer. Therefore, every believer is called tofulfill God’s plan to proclaim the kingdom of God. To find out the divine mandate for preachingGod’s Kingdom, the qualitative method of literature study is used.